2019
DOI: 10.1093/gbe/evz232
|View full text |Cite
|
Sign up to set email alerts
|

The Amount of RNA Editing Sites in Liverwort Organellar Genes Is Correlated with GC Content and Nuclear PPR Protein Diversity

Abstract: RNA editing occurs in the organellar mRNAs of all land plants but the marchantioid liverworts, making liverworts a perfect group for studying the evolution of RNA editing. Here, we profiled the RNA editing of 42 exemplars spanning the ordinal phylogenetic diversity of liverworts, and screened for the nuclear-encoded pentatricopeptide repeat (PPR) proteins in the transcriptome assemblies of these taxa. We identified 7,428 RNA editing sites in 128 organellar genes from 31 non-marchantioid liverwort species, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 56 publications
4
36
1
Order By: Relevance
“…Due to the very large difference between the numbers of predicted and empirically measured RNA editing sites in Taxus (this study) and Welwitschia [81], we did not compare the variation in RNA editing sites among the five focal species in detail. Generally, the number of mitochondrial RNA editing sites is not correlated with mitogenome size or GC content but is significantly correlated with the GC content of genes [53,82]. However, this correlation is not supported in this study.…”
Section: Separate Losses Of Multiple Mitochondrial Trna Genes In Pinacontrasting
confidence: 87%
“…Due to the very large difference between the numbers of predicted and empirically measured RNA editing sites in Taxus (this study) and Welwitschia [81], we did not compare the variation in RNA editing sites among the five focal species in detail. Generally, the number of mitochondrial RNA editing sites is not correlated with mitogenome size or GC content but is significantly correlated with the GC content of genes [53,82]. However, this correlation is not supported in this study.…”
Section: Separate Losses Of Multiple Mitochondrial Trna Genes In Pinacontrasting
confidence: 87%
“…The tRNA genes were annotated using tRNAscan-SE v2.0 [47]. Mitochondrial RNA editing sites were obtained from our previous study on liverwort organellar RNA editing [48]. We summarized and compared the structural evolution of all the formally published (as by June 2019) liverwort mt genomes (Additional file 2: Table S2) from the gff3 annotation files.…”
Section: Methodsmentioning
confidence: 99%
“…Mosses seem to hold the least amount of RNa editing sites, e.g., Physcomitrium holds 11 C-to-u RNa editing events in its mt transcripts (Rüdinger et al 2009). using genomic and transcriptomic data, our previous study (Dong et al 2019b) has identified 4,694 RNa editing sites in the mitogenomes of 33 liverwort species, 91% of these occurring as nonsynonymous editing. The abundance of RNa editing site varies greatly among different liverwort lineages, species, and genes.…”
Section: Bryophyte Mitochondrial Rna Editingmentioning
confidence: 98%
“…Bryophyte mitogenomes demonstrate much smaller sizes (100-242 Kb) with narrow size fluctuations compared with that of the large and variable mitogenomes of vascular plants. each bryophyte lineage holds a constant protein-coding gene (PCg) set with very small variations (Liu et al 2014b;Dong et al 2018a;Dong et al 2019b). Liverworts and mosses hold the most complete mt gene repertoire of 40-42 PCgs among land plants, whereas hornwort mitogenomes show distinctly reduced numbers of functional genes, with most ribosomal protein genes lost or pseudogenized (Dong et al 2018a).…”
Section: Introductionmentioning
confidence: 99%